Consumer Preferences of Ijen Raung’s Coffee Bag - Andi Eko Wiyono; Andrew Setiawan Rusdianto; Meiji Wanarni Putri (Newinera Publisher, 2021)
Coffee bag is pure coffee packaged in a dip bag. The first advantage of this product is that consumers can enjoy black coffee with the right taste because it already has a one-time dose. Some drinkers who do not pay attention to the rest of the coffee, by consuming coffee bag they will not get the remaining coffee grounds in their drinks. This study have purpose to see the attributes that become preferences and indicators that measure the taste of the best variation of coffee bag that consumers want. The result of this research is that the coffee is dyed based on consumer preference which is coffee that has a bitter taste, an aroma that represents the taste of coffee, a strong mouth weight, and a long-lasting taste. The taste of the coffee bag with the best variation that consumer input is the natural sample, namely 4169 100% natural coffee bag with an average of 3.79. Respondents argued that the natural sample has a strong mouth weight, bitter taste, and the aroma of the sample represents coffee (has a characteristic). Coffee produced from the dry process is usually superior in the body, fruity taste (fruity), more bitter, low acidity.